Advances in Organic and Perovskite Photovoltaics Enabling a Greener Internet of Things. (9th April 2022) - Panidi, Julianna; Georgiadou, Dimitra G.; Schoetz, Theresa; Prodromakis, Themis
Abstract: Organic and perovskite solar cells (PSCs) have made significant strides in the last couple of years achieving high power conversion efficiencies (18% and 29%, respectively) and exceptional stability. Ultra‐flexible and environmentally stable organic and PSCs can effectively operate under various illumination settings. Herein, novel device concepts that comprise photovoltaic cells alone or in tandem with batteries or supercapacitors, acting as the main power supply to another microelectronic component, enabling self‐powered electronics for the Internet of Things (IoT) are reviewed. Emphasis is placed on the specific requirements posed by such applications to pave the way to large scale commercialization. The importance of supporting a greener IoT ecosystem by eliminating toxic materials and solvents in the device fabrication process is highlighted. Abstract : Self‐powered devices application range has increased drastically over the past few years, including smart clothing and wearable devices, agrivoltaics, industrial Internet of Things (IoT) and structural monitoring in hard‐to‐reach areas. Utilizing indoor and outdoor light to power electronics using emerging photovoltaic technologies based on organic and perovskite non‐toxic materials fabricated with eco‐friendly processes will contribute to a greener IoT ecosystem.